A "Stretchier" Kind of Witnessing: Turning Nazi Psychiatric Killing Centers into Memorials. Issue 3 (1st August 2022) - Mitchell, David T.; Snyder, Sharon L.
Abstract : The article compiles the events marking the precarity of disabled peoples' lives during the Second World War in Germany through an examination of the transition of Nazi psychiatric killing centers into memorials during the long twentieth century. As Judith Butler points out in Frames of War: When is Life Grievable?, recognizing the conditions of vulnerability calls us to a responsibility to alter abuse, suffering, and violence; yet it may also be true that "the apprehension of precariousness leads to a heightening of violence, [as] an insight into the physical vulnerability of some set of others […] and incites the desire to destroy them" (2). Such is the case with the medical mass murder of 300, 000+ psychiatric patients in Nazi Germany as this preliminary medical mass murder made possible the post-1941 Holocaust genocide of 5.4 million Jewish people in death camp gas chambers. Thus, the article attempts to answer some critical questions by using Nazi medical mass murder as its historical foundation: How does one witness a violent mass tragedy when no witnesses survived? What meaning can be derived from the memorialization of disability history in our own contemporary moment? What do these public acts of recognition mean to disabled people as a group and/or disability scholars as part of the preservation of disability history? Why do these medical mass killings that pre-date and lead to the Holocaust still sit primarily unrecognized and forgotten? Finally, what do today's memorialization practices tell us about contemporary attitudes toward disability as this largely unaffiliated subpopulation lives in the aftermath of this murderous history? When and how do disabled lives become grievable? How might we devise an alternative model to Holocaust studies' pivotal reliance on direct witnesses that are not available in the Aktion T4 psychiatric killings?